„A mürcüs az enyim!” Lénárd Róbert: „Pajzán históriák” (Tanyaszínház, 2014) - Tamás Oláh (Symbolon, 2021)
“Mürcüs is Mine!” Róbert Lénárd: „Impish Stories” [Pajzán históriák] (Tanyaszínház [Hamlet’s Theater], 2014) The population of the Hungarians in Vojvodina is drastically declining. In order to stop this process, in 2013 the Hungarian National Council (Magyar Nemzeti Tanács) developed a strategy called the Population Action Plan (Népesedési Akcióterv), which offered solutions to the Hungarian-speaking, fertile population of the province. A year later, the Hamlet’s Theater’s (Tanyaszínház) company under the direction of Róbert Lénárd examined the biopolitical aspects of the action plan and made a memorable performance using several erotic folk tales from Vojvodina.